Patellar Tendon Reflex and Vastus Medialis Hoffmann Reflex Are Down Regulated and Correlated in Women With Patellofemoral Pain - Pazzinatto, Marcella Ferraz [UNESP]; de Oliveira Silva, Danilo [UNESP]; Ferreira, Amanda Schenatto [UNESP]; Waiteman, Marina Cabral [UNESP]; Pappas, Evangelos; Magalhães, Fernando Henrique; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2018)
Objectives: The aims of this study were threefold: (1) to compare the amplitude of patellar tendon reflex (T-reflex) between women with patellofemoral pain (PFP) and pain-free controls; (2) to compare the amplitude of vastus medialis Hoffmann reflex (VM H-reflex) between women with PFP and pain-free controls; (3) to investigate the association between the amplitude of patellar T-reflex and VM H-reflex in women with PFP and pain-free controls. Design: Cross-sectional observational study. Setting: Laboratory of biomechanics and motor control. Participants: Thirty women with PFP and 30 pain-free women aged 18 to 35 years (N=60). Main Outcome Measures: Peak-to-peak amplitudes of maximal VM H-reflex (elicited via electrical stimulation on the femoral nerve) and patellar T-reflex (elicited via mechanical percussion on the patellar tendon) were estimated. Results: Women with PFP had significant lower amplitude of patellar T-reflex (mean difference=0.086; 95% confidence interval=0.020 to 0.151; P=.010; moderate effect) and VM H-reflex (mean difference=0.150; 95% confidence interval =0.073 to 0.227; P<.001; large effect) compared to pain-free controls. The VM H-reflex was strongly correlated with patellar T-reflex in both PFP group (r=0.66; P<.001) and control group (r=0.72; P<.001). Conclusions: As the T-reflex is easier to perform than H-reflex assessments in a clinical setting, it represents a feasible option to assess the impaired excitability of the stretch reflex pathway associated with PFP.
Keywords: Inhibition; Knee; Motor neurons; Rehabilitation; Stretch reflex